Management and Complications of Cerebral Malaria - Putra, Rifky Sandya Rakadi; Retnaningsih, Ekawaty; Kadarisma, Shofia; Sesariana, Mayumi Agestia; Syalsabila, Dara Pitra; Karlina, Fairuz (Universitas Ibn Khaldun Bogor, 2025)
Malaria remains a major public health issue in Indonesia, particularly in regions with high endemicity such as Papua and East Nusa Tenggara. According to the 2010 Basic Health Research (Riskesdas), the national malaria prevalence was 0.6%, with the highest rates recorded in West Papua (10.6%), Papua (10.1%), and East Nusa Tenggara (4.4%). In 2023, Papua continued to be identified as a region with high endemicity, while West Nusa Tenggara was classified as having low endemicity. Severe malaria, including cerebral malaria, is a serious complication characterized by central nervous system dysfunction, such as decline consciousness, seizures, and neurocognitive impairment, as well as systemic complications such as anemia, hypoglycemia, metabolic acidosis, and hepatosplenomegaly. Management of severe malaria requires the administration of antimalarial injections, such as intravenous artesunate as the first line therapy or quinine drip if artesunate is unavailable, performed in healthcare facilities equipped with inpatient care and intensive monitoring. This procedure involves close monitoring of blood pressure, temperature, blood glucose levels, and organ function to prevent further complications. The prognosis of cerebral malaria patients depends on the timeliness of diagnosis and proper management, while comprehensive care can improve recovery rates and reduce long-term risks. Preventive efforts through strengthening healthcare facilities in endemic areas and increasing public awareness is crucial to reduce the incidence of severe malaria and its adverse effects.